Automated Incubation and Digital Image Analysis of Chromogenic Media Using Copan WASPLab Enables Rapid Detection of Vancomycin-Resistant Enterococcus - Cherkaoui, Abdessalam; Renzi, Gesuele; Charretier, Yannick; Blanc, Dominique S.; Vuilleumier, Nicolas; Schrenzel, Jacques (Frontiers in Cellular and Infection Microbiology, 2019)
Objective: The aim of the present study was to assess whether the WASPLab automation enables faster detection of vancomycin-resistant Enterococcus (VRE) on chromogenic VRE-specific plates by shortening the incubation time. Methods: Ninety different VRE culture negative rectal ESwab specimens were spiked with various concentrations (ranging from 3x102 to 3x107 CFU/ml) of 10 Enterococcus faecium strains (vancomycin MICs ranging from 32 to >256 mg/l), 3 E. faecium VanB strains (vancomycin MICs: 4, 8, and 16 mg/l), and 2 E. faecium VanB strains displaying vancomycin heteroresistance (vancomycin MICs: 64 and 96 mg/l). Results: Besides the two strains exhibiting vancomycin heteroresistance, all the other 13 VRE strains included in this study were detected as early as 24h on the WASPLab even if the inoculum was low (3x103 CFU/ml). When the vancomycin MICs were high, all strains were detected as early as at 18h. However, 30h was a conservative time point for finalizing the analysis of chromogenic cultures. Conclusion: These results suggested that the WASPLab automated incubation could allow decreasing the initial incubation time to 18h, followed by an intermediate time at 24h and a final incubation period of 30h for VRE culture screening, to deliver rapid results without affecting the analytical sensitivity.